Public Expenditure and Economic Growth of Nepal (The Lumbini Journal of Business and Economics, 2022)
This paper examines the effect of public expenditure and economic growth of Nepal over the period of 1975-2021. The public expenditure of Nepal has been significantly increasing during the study period. The objective of this study is to examine the impact of public expenditure on economic growth of Nepal by ARDL and ECM model. Descriptive and analytical research design has been used by using secondary data. The finding of the study concluded that growth in education expenditure and agriculture expenditure has negative and positively significantly impact on the growth in GDP respectively at 5% level of significance. Health expenditure and communication and transport expenditure has positive and negative insignificant effect economic growth respectively. The findings of this study revealed that increase in agriculture expenditure increases the growth of the economy of Nepal. Public expenditure should be best allocated for the development of transpiration, communication and social service in order to reduce geographical fragmentation and increase the profitability of private investment as well as by extending the size of the market, skill and efficiency of labor.